A sulfur-containing two-dimensional covalent organic framework with electrocatalytic hydrogen evolution in alkaline medium. Issue 42 (6th October 2022) - Ma, Yunchao; Fu, Yue; Han, Yuhang; Li, Jingyang; Jiang, Wei; Lu, Yang; Liu, Chunbo; Che, Guangbo; Hu, Bo
Abstract : In this work, we successfully synthesized metal-free 2D COF electrocatalysts with high hydrogen evolution performance in alkaline solution. The overpotential is 290 mV at 10 mA cm −2 with small Tafel slopes. Abstract : At present, the electrocatalytic hydrogen evolution reaction (HER) has been widely studied in the field of energy and resource conversion. Herein, a metal-free sulfur-containing covalent organic framework material (JLNU-300 ) was designed and synthesized using thieno[3, 2- b ]thiophene-2, 5-dicarboxaldehyde (TTDC) as an efficient electrocatalyst for the hydrogen evolution reaction in alkaline solution. The test analysis results showed that JLNU-300 had high crystallinity and specific surface area (298.99 m 2 g −1 ). In addition, the material has high electrocatalytic hydrogen evolution reaction (HER) activity, with an overpotential value of 290 mV and a Tafel slope of 99 mv dec −1 at a current density of 10 mA cm −2 . The introduction of thiophene groups effectively changed the electronic structure and chemical properties of the COF framework, and the high crystallinity and specific surface area of the COF itself increased the effective contact area between reactants and active points, thus promoting the HER process. The results show that the reasonable structure design of COFs can further promote their wide application in the field of electrocatalysis.